Navigating borders and transgressing boundaries: a feminist autoethnography - Louis, Heidi (My University, 2025)
In this autoethnography, I explore the intersections of my lived experiences, systemic inequity, and educational practice through the lens of critical feminism. Grounded in my encounters with the carceral system and punitive school discipline, this study examines how those experiences shape my philosophy, leadership, and commitment to restorative justice in education. Guided by three questions—how my experiences with the carceral system and punitive discipline inform my educational practice, and how my understanding of discipline evolves across the intersectional spaces of my life—I use critical reflection and narrative inquiry to analyze the personal and political dimensions of schooling and justice. Through this process, I position myself as both researcher and subject, interrogating the carceral logics embedded in educational systems and illuminating the transformative potential of restorative approaches. My analysis reveals that growth and understanding emerge through self-examination, resistance to oppressive structures, and the reclamation of voice and agency. This study contributes to the broader discourse on educational equity by centering lived experience as a site of knowledge production and by advocating for practices rooted in empathy, relational accountability, and systemic transformation.
Keywords: Restorative justice; Punitive discipline; Carceral; Education